Nodular Fasciitis of the Breast Mimicking Breast Cancer - Shinya Yamamoto; Takashi Chishima; Shouko Adachi (Case Reports in Surgery, 2014)
Nodular fasciitis is a benign proliferative lesion that is usually found in the soft tissue of the upper extremity and trunk in young to middle-aged persons. It has rarely been described in the breast. A 35-year-old woman had noticed a mass in her left breast. It was elastic-hard, 13 mm in size, and located mainly in the upper inner quadrant of the left breast. Mammography did not detect the mass. Ultrasonography revealed a hypoechoic lesion with an irregular margin. Neither fine-needle aspiration cytology nor core needle biopsy established a definitive diagnosis. Excisional biopsy was therefore performed. Histologically, the excised tumor tissue results were consistent with a diagnosis of nodular fasciitis of the breast. We report a case of nodular fasciitis of the breast, a rare histological type of breast tumor.